Pelayanan Gereja: Kebutuhan Pendampingan Pastoral Pada Keluarga Yang Memiliki Anak Berkebutuhan Khusus (Studi Kasus Tunadaksa) - Retno Dwi Hastuti (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2023)
This study aims to look at the picture of the struggles of families who have children with special needs, especially the disabled. On the other hand, we also want to see how far the church's pastoral assistance is for families who have children with physical disabilities. The research method used in this research is a qualitative approach. While data collection is done through observation, interviews and documentation. Based on the results of research and data analysis, families still do not fully and deeply understand disabled persons, their characteristics and the accompanying impacts. Thus, families are often not ready to deal with the emotions of children with physical disabilities. Pastoral assistance from the church has not touched the struggles that are being experienced by families.